Review of Young Marriages According to Islamic Law in Liang Country, Salahutu District, Central Maluku Regency - Erni Mizan; Louisa M. Metekohy; Jumiati Tuharea (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
This study aims to find out and obtain results related to the review of young marriages according to Islamic law in the liang country of salahutu district, Central Maluku regency. This research covers how Islamic law views young marriage and the impact of young marriage in a family. This type of research is qualitative using descriptive methods. The data collection techniques used are observation, interviews, and documentation. The information of this study was determined by purposive sampling. The data analysis technique used is descriptive qualitative through data collection, data reduction, data presentation, and conclusions so that a systematic series is arranged. The results of this study show that in the implementation of marriage at a young age according to the view of Islamic Law and The Number Act. 1 The year 1974 is justified and has the element of allowing for the good of those who marry at a young age, thus if strong and accountable reasons are found by both parties. The impact of marriage at a young age is an influence that affects the course of marital relations in the household ark, many of the impacts that affect marriage can be seen from the elements of economy, readiness, and knowledge. So before marriage, it is necessary to have readiness and maturity of each of them both mentally and materially. So that the marriage can go well.